Stressor-Induced Reduction in Cognitive Behavior is Associated with Impaired Colonic Mucus Layer Integrity and is Dependent Upon the LPS-Binding Protein Receptor CD14 - Jaggers RM; DiSabato DJ; Loman BR; Kontic D; Spencer KD; Allen JM; Godbout JP; Quan N; Gur TL; Bailey MT (Dove Medical Press, 2022)
Robert M Jaggers,1 Damon J DiSabato,2,3 Brett R Loman,1 Danica Kontic,1 Kyle D Spencer,1,4,5 Jacob M Allen,1 Jonathan P Godbout,2,3 Ning Quan,6 Tamar L Gur,2,7 Michael T Bailey1,2,8 1Center for Microbial Pathogenesis, Abigail Wexner Research Institute at Nationwide Children's Hospital, Columbus, OH, 43205, USA; 2Institute for Behavioral Medicine Research, Columbus, OH, 43210, USA; 3Department of Neuroscience, The Ohio State University, Columbus, OH, 43210, USA; 4Department of Biomedical Informatics, The Ohio State University, Columbus, OH, USA; 5Graduate Partnership Program, National Center for Advancing Translational Sciences, National Institutes of Health, Bethesda, OH, USA; 6Department of Biomedical Science, Charles E. Schmidt College of Medicine, Florida Atlantic University, Jupiter, FL, 33458, USA; 7Department of Psychiatry, College of Medicine, The Ohio State University, Columbus, OH, 43210, USA; 8Department of Pediatrics, College of Medicine, The Ohio State University, Columbus, OH, 43210, USACorrespondence: Michael T Bailey, Center for Microbial Pathogenesis, Abigail Wexner Research Institute, W410, Nationwide Children's Hospital, 700 Children's Drive, Columbus, OH, 43205, USA, Tel +1 614-722-2764, Email Michael.bailey2@nationwidechildrens.orgPurpose: Commensal microbes are impacted by stressor exposure and are known contributors to cognitive and social behaviors, but the pathways through which gut microbes influence stressor-induced behavioral changes are mostly unknown. A murine social stressor was used to determine whether host-microbe interactions are necessary for stressor-induced inflammation, including neuroinflammation, that leads to reduced cognitive and social behavior.Methods: C57BL/6 male mice were exposed to a paired fighting social stressor over a 1 hr period for 6 consecutive days. Y-maze and social interaction behaviors were tested following the last day of the stressor. Serum cytokines and lipopolysaccharide binding protein (LBP) were measured and the number and morphology of hippocampal microglia determined via immunohistochemistry. Intestinal mucous thickness and antimicrobial peptide expression were determined via fluorescent staining and real-time PCR (respectively) and microbial community composition was assessed using 16S rRNA gene amplicon sequencing. To determine whether the microbiota or the LBP receptor (CD14) are necessary for stressor-induced behavioral changes, experiments were performed in mice treated with a broad-spectrum antibiotic cocktail or in CD14−/− mice.Results: The stressor reduced Y-maze spontaneous alternations, which was accompanied by increased microglia in the hippocampus, increased circulating cytokines (eg, IL-6, TNF-α) and LBP, and reduced intestinal mucus thickness while increasing antimicrobial peptides and cytokines. These stressor-induced changes were largely prevented in mice given broad-spectrum antibiotics and in CD14−/− mice. In contrast, social stressor-induced alterations of social behavior were not microbe-dependent.Conclusion: Stressor-induced cognitive deficits involve enhanced bacterial interaction with the intestine, leading to low-grade, CD14-dependent, inflammation.Keywords: social defeat, stress, microbiome, microglia, cytokines, neuroinflammation, mucus barrier